Do disque denúncia ao call center : os limites do Disque 100 para a realização da denúncia de violência contra a população LGBT - Nicole Gonçalves da Costa (2016)
Studies on the flows of complaint constitute a gap in the field of studies on homophobic/transphobic violences in Brazil, especially in terms of public security policies, geared to the specific characteristics of violence and rights violations experienced by LGBT population. Through documentary research, it was intended to accomplish a mapping of the forwarding flow of violence against LGBT people, in view of the Dial 100 LGBT module or Dial Human Rights in Minas Gerais, linked to the National System for Promotion of Rights and Combating Violence Against Lesbian, Gay, Bisexual and Transgender. It sought to understand how the complaint is processed within the legal institution and which determinants produce interruptions in the flow, compromising the proper functioning of the service. It was found that the Dial 100, in despite of having a reporting module designed specifically for the LGBT public, hasn't been able to take the complaint of this population on. The complaint does not arrive directly to the official equipment, for the field of legitimacy, intelligibility, to actually be heard by the government. Instead, the service has been itself an impediment to the complaint.